Barrett's Esophagus - Irfan Maulani; Murdani Abdullah; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Barrett’s esophagus (BE) is a predisposing factor of esophageal adenocarcinoma. Metaplasia on BE occurs due to imbalance between esophageal defensive and reluxate materials offensive factors. Nowadays, it is believed that gastroesophageal reflux disease (GERD) is one of major risk factors of BE. Patients with BE generally have lower esophageal sphincter (LES) pressure, shorter LES and intra- abdominal esophageal length, and longer acid exposure than patients with severe esophagitis. Acid exposure has pro-proliferation and anti-apoptosis effect which can facilitate BE occurrence. Currently BE management has gone through various advance, especially in its diagnostic section, from the development of sophisticated endoscopic modality to the finding of biomarker to predict cancer occurrence on BE. Therapeutic section has also been progressing, especially with its endoscopic and chemoprevention therapy. This review article addresses the latest update of BE management.   Keywords: Barrett’s esophagus, GERD, management